2019
DOI: 10.3389/fphys.2019.01276
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Clusters of Competitive Cyclists and Their Sprint and Endurance Performance

Abstract: Do athletes specialize toward sports disciplines that are well aligned with their anthropometry? Novel machine-learning algorithms now enable scientists to cluster athletes based on their individual anthropometry while integrating multiple anthropometric dimensions, which may provide new perspectives on anthropometry-dependent sports specialization. We aimed to identify clusters of competitive cyclists based on their individual anthropometry using multiple anthropometric measures, and to evaluate whether athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
1
24
0
3
Order By: Relevance
“…Both ultrasound and myotonometry showed good to excellent relative reliability. These findings are interpreted in relation to the anthropometrics characteristics of sprint track cyclists (Van Der Zwaard et al, 2019) and competition characteristics (Craig and Norton, 2001) as well as with respect to the risk of getting injury. Qt Thick , quadriceps tendon thickness; Pt Thick , patellar tendon thickness; PT Stiff , patellar tendon stiffness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both ultrasound and myotonometry showed good to excellent relative reliability. These findings are interpreted in relation to the anthropometrics characteristics of sprint track cyclists (Van Der Zwaard et al, 2019) and competition characteristics (Craig and Norton, 2001) as well as with respect to the risk of getting injury. Qt Thick , quadriceps tendon thickness; Pt Thick , patellar tendon thickness; PT Stiff , patellar tendon stiffness.…”
Section: Discussionmentioning
confidence: 96%
“…Sprint and endurance track cyclists have different anthropometric characteristics, muscle's mechanical properties, and fiber type composition. For instance, sprinters exhibit greater thigh girths but shorter thigh lengths (Van Der Zwaard et al, 2019 ) and their quadriceps muscle contains predominantly fast-twitch fibers (Loturco et al, 2015 ). Cyclists are more exposed to tendon injuries (i.e., patellar quadriceps tendinopathies) than muscle sprains (Wanich et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second aim of this study was to determine if there was a statistical association between the MCT1 A1470T polymorphism and the high-intensity performance in nonpower-trained athletes. The PP and MP output during a WAnT indicated that participants of our study showed excellent fitness (see results in Table 2 ) according to available data from endurance-trained cyclists/triathletes [ 34 , 35 ]. Although the sample size could limit the detection of small genetic effects of this SNP on high-intensity endurance, no significant differences were found between the MCT1 A1470T polymorphism and the measured physical variables.…”
Section: Discussionmentioning
confidence: 62%
“…Morphological research has been widely used in road cycling [ 11 , 12 , 13 , 14 , 15 , 16 ]. As one of the sports with repetitive movements, cycling can cause muscle force and/or flexibility asymmetries [ 17 , 18 ], leading to morphological asymmetries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%